Problems of Business Education in High School Students : Systematic Literature Review (SLR) - Shofia Azahra; Akha Anis Fitriah; Nurul Wahyuni; Ludi Wishnu Wardana; Aniek Indrawati; Bagus Setiawan; Dieva Zahrohtu Anfi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
Business education should have started from the beginning of education, one of which is at the high school level. Currently in Indonesia itself, entrepreneurship subjects are also one of the subjects that must be taken by high school students. This research is a systematic literature review (SLR) that discusses business education problems in high school students. Literature study research is a process or activity of collecting data from various literatures such as books and journals to compare the results of one research with another. There are 10 articles related to business education problems in high school students, these 7 journals will be used in answering the next problem formulation. From several articles that have been reviewed, there are several determinants of business education problems in high school students including the influence of the school environment, community environment and lack of student knowledge and students' emotional attitudes.